A new species of Cedrela (Meliaceae) from the eastern flanks of Ecuador - Palacios, Walter A.; Santiana, Janeth; Iglesias, Juan (Phytotaxa, 2019)
A new species, Cedrela domatifolia, is described. It is characterized by the leaves of 55–80 cm long, leaflets 10–15 pairs, this oblong-lanceolate, 15–25 cm long × 4–8 cm wide, with prominent and inflated domatium on the axes of the secondary veins on the underside; calyx shortly cupuliform, 2.3–2.5 mm long, 5-lobed, one side (in open flower, not in bud) split down to the base; corolla purple-reddish with the margin and apex cream, and bearded inside. The new species is a tree that reaches 40 m in height and is only known from the eastern slopes of Ecuador, between 800 and 1100 m approximately. It grows exclusively on black laminar rocks, slate type, and has a strong and unpleasant smell of garlic, more noticeable than in other species of the genus. The most related species is C. nebulosa, but with smaller leaflets without domatium. The distribution area of the first one is enclosed within the second.